Do Cross-border Acquisitions involving Emerging Market Firms Create Value: Impact of Deal Characteristics. Issue 8 (20th August 2014) - Narayan, P.C.; Thenmozhi, M
Abstract : Purpose: This study contributes to M&A literature by explicitly investigating whether cross-border acquisitions involving emerging markets, either as acquirers or as targets, create value and how is the performance outcome in such acquisitions impacted by deal-specific characteristics. Design/methodology/approach: This study uses industry-adjusted operating performance to measure acquisition gains, the Wilcoxon signed rank test to examine value creation potential and OLS regression to evaluate the impact of deal characteristics on acquisition gains. Findings: We find very pronounced value destruction when emerging market firms acquire targets in developed markets, the adverse outcome being further aggravated when the mode of acquisition is 'tender offer' rather than a 'negotiated deal'. On the other hand, when developed market firms acquire targets from emerging markets, there is an even chance of value creation, the outcome being favorably influenced by the per-acquisition performance of the two firms, relative size of the target and cash (not stock-swap) as the mode of payment. Originality/value: The findings from this study offer an important, statistically significant explanation on the value creation potential and the impact of deal characteristics on post-acquisition operating performance in cross-border acquisitions involving emerging market firms. This finding assumes immense significance, given the rapidly changing landscape of global M&A, witnessed through a continuous rise in the volume and value of cross-border acquisitions involving emerging market firms.